Elliptic Curves, Modular Forms and Iwasawa Theory: In Honour of John H. Coates' 70th Birthday, Cambridge, UK, March 2015 - Loeffler, David; Zerbes, Sarah Livia (Springer, 2016)
1. A.Berti, M.Bertolini, R.Venerucci: Congruences between modular forms and the Birch and Swinnerton-Dyer conjecture -- 2. T.Bouganis: P-adic measures for Hermitian modular forms and the Rankin–Selberg method -- 3. A.Conti, A.Iovita, J.Tilouine: Big image of Galois representations associated with finite slope p-adic families of modular forms -- 4. A.Dabrowski: Behaviour of the order of Tate–Shafarevich groups for the quadratic twists of X0(49) -- 5. T.Fukaya, K.Kato, R.Sharifi: Compactifications of S-arithmetic quotients for the projective general linear group -- 6. R.Greenberg: On the structure of Selmer groups -- 7. H.Hida: Control of Lambda-adic Mordell-Weil groups -- 8. M.Kakde: Some congruences for non-CM elliptic curves -- 9. M.Kim: Diophantine geometry and non-abelian reciprocity laws I -- 10. G.Kings: On p-adic interpolation of motivic Eisenstein classes -- 11. T. Lawson, C.Wuthrich: Vanishing of some Galois cohomology groups for elliptic curves -- 12. P.Schneider, O.Venjakob: Coates–Wiles homomorphisms and Iwasawa cohomology for Lubin–Tate extensions -- 13. A.Wiles, A.Snowden: Big image in compatible systems.
Keywords: Konferenzschrift